2015
DOI: 10.1117/12.2082909
|View full text |Cite
|
Sign up to set email alerts
|

3D statistical shape models incorporating 3D random forest regression voting for robust CT liver segmentation

Abstract: During image segmentation, 3D Statistical Shape Models (SSM) usually conduct a limited search for target landmarks within one-dimensional search profiles perpendicular to the model surface. In addition, landmark appearance is modeled only locally based on linear profiles and weak learners, altogether leading to segmentation errors from landmark ambiguities and limited search coverage. We present a new method for 3D SSM segmentation based on 3D Random Forest Regression Voting. For each surface landmark, a Rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…The mean error in the first metacarpal was 0.997 mm ± 0.372 mm, and 0.564 mm ± 0.282 mm in the trapezium, which may be considered reasonable depending on the purpose of the model. The mean % volume overlap was 84.12 % in the first metacarpal and 86.03 % in the trapezium, is comparable to the intermediate rigid model fitting results on the liver reported by Norajitra, Meinzer and Maier-Hein (2015), except in a much smaller joint. However, for the purpose of contact biomechanics at the articular surfaces of the joint, these errors may require further reduction, as the maximum errors (2.110 mm in the first metacarpal and 1.776 mm in the trapezium) are comparable to the size of the joint space in the TMC joint (~ 2 mm).…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…The mean error in the first metacarpal was 0.997 mm ± 0.372 mm, and 0.564 mm ± 0.282 mm in the trapezium, which may be considered reasonable depending on the purpose of the model. The mean % volume overlap was 84.12 % in the first metacarpal and 86.03 % in the trapezium, is comparable to the intermediate rigid model fitting results on the liver reported by Norajitra, Meinzer and Maier-Hein (2015), except in a much smaller joint. However, for the purpose of contact biomechanics at the articular surfaces of the joint, these errors may require further reduction, as the maximum errors (2.110 mm in the first metacarpal and 1.776 mm in the trapezium) are comparable to the size of the joint space in the TMC joint (~ 2 mm).…”
Section: Discussionsupporting
confidence: 82%
“…3D Haar-like features) to train a forest of decision trees to predict the most likely image location of the desired model. This has been demonstrated in 2D with facial recognition (Cootes et al 2012) and 2D segmentation of the proximal femur (Lindner et al 2013), and more recently demonstrated in 3D in the Liver (Norajitra et al 2015). This method can be combined with parametric statistical shape modelling to create an automatic segmentation pipeline that has increased robustness to initialisation, increased speed of segmentation, and automatic meshing for downstream analysis.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…Despite the development of various automated segmentation methods, including heuristically customized appearance models and automatic selection of optimal local features [41], these methods are limited by their reliance on local image information and the use of heuristic or weak learning methods [40,42]. However, models utilizing randomized regression forests have emerged, offering robust learning that consider non-local image information and omni-directional landmark detection, thereby enhancing segmentation accuracy and robustness across various organs without the need for prior model initialization [40,[43][44][45].…”
Section: Introductionmentioning
confidence: 99%